(3HOjYjI GHf MLI GdMehjs - (3CHh HcQ Hf Ydj Hf YHO Gddg GdMehj GdCRQGQj, Jbj GdOjf GHf MLI , (B837 (3g` s ((3ehQhj MGaX eMeO UGOb Yhfjs)
(3ChdgG (B:s
(3bGd GdUaj GdMdj GdcGajI GdHOjYI aj GdeOGFM GdfHhjI HQGYI GdGSJgdGd hJLfjS GdeQcH hGdeTHgCf LFJ SdYG aSd Yf LjQI GdYde hCbQj GdSdGe Ydi YQH HPj Sdes
(3BNQgG (B:s
(3HQGYI GdNJGe, aEf SYOJ aeOMj ajc ehLHg (B*** (3hEf TbjJ aPfHj ehLH Gdfbes
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B: 2 / 67s
(3eYLe GdeDdajf(B: 1 / 441s
(3cTa GdXfhf(B: 1 / 233s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
Keywords: (3GdCOHs